Pelatihan Safety Leadership dan Resilience pada Perusahaan Engineering dengan Pendekatan Pembelajaran Interaktif Berbasis Web - Agung Raharjo; Ariyanto, Januar; Suparni; Farahul Jannah (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2025)
Safety management in high-risk industries often focuses on reactive risk prevention, making it difficult to anticipate unforeseen challenges in complex projects. While a shift toward resilience-based safety emphasizes adaptability, practical implementation remains a challenge. This community engagement project aimed to improve safety leadership and resilience through interactive training, integrating video-based scenarios and web-based interactive tools. The training involved 18 employees from a target company. Post-test scores demonstrated significant improvement, with the average score rising from 5.5 to 8.13, indicating enhanced understanding of safety leadership and resilience principles